# Reducing Equations to Simpler Form

**Example 3: Solve**

- Multiplying both sides of the equation by 6
- On simplifying the divisions
- Solving for terms within the brackets
- Solving the constant terms on LHS.
- Move x to one side of the equation to simplify.
- Simplify for the
*x*vaiable - Now, simplify the constant terms
- Solve the constant terms on the RHS
- We get: x =
- Thus, x =
is the solution.

Now, that we have found the solution, let's check if the LHS and RHS of the equation are equal or not.

**Now check the LHS and RHS of the above expression by substituting the obtained x value.**

**Example 4: Solve 5x – 2 (2x – 7) = 2 (3x – 1) + **

- Solving the terms with brackets
- This can be further simplified
- Solving for the constant terms on RHS.
- Transposing the constant to the LHS and
*x*to RHS - Solving we get
- Now, we have
- We get: x =
- Therefore, required solution is x =

**Check:** LHS = 5 ×

=

RHS = 2(

=